An Examination of Nurses' Understanding and Experience with Enteral Tube Drug Delivery - Ahmed Abdulmohsen Alhamoud,; Mohammed Dawood Alkhalaf,; Nahlah Mubark Alotaibi,; Ali Nassir Al Atafi,; Meshal Saeed Almudairis,; Zahra Hussain Ali Bu Hassun,; Horyah Ali Busaleh,; Aminah Ali Busaleh,; Mohammed Ibrahiem Almukaideer,; Murtadha Essa Ali Alhafed, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Enteral tubes are critical for delivering artificial nutrition, hydration (ANH), and medications to patients. However, practical challenges such as tube blockages, improper medication administration practices, and insufficient training can compromise patient care and increase healthcare costs. Research has highlighted the need for improved education, equipment, and institutional support to enhance medication delivery through enteral tubes. Methods: This descriptive, exploratory study utilized a self-reported survey distributed to 150 registered nurses in medical, surgical, and intensive care wards. The survey included 28 items covering knowledge, practices, challenges, and training regarding medication administration via enteral feeding tubes. Data were analyzed using Microsoft Excel™, and thematic analysis was conducted to identify patterns and challenges. Results: A total of 73 nurses (48.7% response rate) participated, with 64% reporting over five years of experience in administering medications via enteral tubes. Nearly half (45%) had not received training in medication administration for enteral feeding, while 44% of training occurred over five years ago. Most nurses (96%) recognized the importance of flushing feeding tubes, yet only 77% consistently practiced this. Challenges included tube blockages (52% required replacement), limited access to liquid formulations, and insufficient equipment such as connectors and clamps. Nurses also highlighted the time-consuming nature of medication preparation, particularly with proton-pump inhibitors and lactulose. Suggested improvements included enhanced training, better equipment, simplified guidelines, and coordinated medication sourcing. Conclusion: The study identified significant gaps in training, resources, and support for nurses administering medications via enteral tubes. Addressing these challenges through multidisciplinary training programs, improved equipment availability, and streamlined guidelines is essential for ensuring safe and efficient care. Enhanced collaboration between nursing, pharmacy, and prescribing teams can further optimize practices and reduce complications associated with enteral tube medication administration.